Konsep Pengaturan Kontinuitas Koalisi Partai Politik Dari Pre-election Coalition Ke Government Coalition (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
The regulation concerning political party coalitions of the presidential election has been implemented since the enactment of Article 6A paragraph (2) of the 1945 Constitution of the Republic of Indonesia. It has been known that in the practice of coalitions formed is relatively short-term and unstable. This study aims to analyze the existence of a pre-election coalition in the presidential election and to examine the concept of formed coalition continuation from the pre-election to become the government steady coalition. Conceptual, comparative, and statute approach are used in this study as a normative legal method research. The research result showed that the continuity of the pre-election coalition in government administration is in line with the purpose of Article 8 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. In addition, to strengthen the binding power of the coalition, it is necessary to set regulations in the forthcoming election law by adding an agreement clause to transform the pre-election coalition into a government coalition. Keywords: continuity; government coalition; political party coalition; pre-election coalition Abstrak Pengaturan koalisi partai politik pada pemilihan presiden mulai terlaksana sejak berlakunya Pasal 6A ayat (2) UUD NRI 1945. Praktik koalisi partai politik yang terbentuk masih bersifat jangka pendek dan tidak stabil. Penelitian ini bertujuan menganalisis eksistensi pre-election coalition pada pemilihan presiden serta mengkaji konsep pengaturan kontinuitas koalisi partai politik dari pre-election coalition ke government coalition. Penelitian ini menggunakan metode penelitian hukum normatif melalui pendekatan konseptual, pendekatan perbandingan dan pendekatan perundang-undangan. Hasil penelitian menerangkan pertama, kontinuitas pre-election coalition dalam penyelenggaraan pemerintahan selaras dengan ketentuan Pasal 8 ayat (3) UUD NRI 1945. Kedua, penguatan daya ikat antar koalisi partai politik membutuhkan pengaturan dalam undang-undang pemilu di masa mendatang melalui penambahan klausul kesepakatan transformasi pre-election coalition menjadi government coalition. Kata kunci: government coalition; koalisi partai politik; kontinuitas; pre-election coalition